BIOPHILIC ARCHITECTURE APPROACH FOR A THE SCIENCE LIBRARY IN MEDAN CITY AS A LEARNING AND KNOWLEDGE PRODUCTION TO ENHANCE USER PRODUCTIVITY - Fairuzna Zahira Dalimunthe; Hajar Suwantoro (Jurnal Ilmiah Multidisiplin Ilmu, 2026)
The low level of science literacy and utilization of public educational facilities in Indonesia, particularly in the city of Medan, demonstrates the need for the development of more productive and human-centered learning spaces. Science libraries no longer function solely as repositories of information, but have evolved into active, collaborative learning spaces and centers for knowledge production. This study aims to examine the application of biophilic architecture in the design of science libraries as an attempt to increase user productivity. This study is qualitative and based on literature reviews and case studies of educational buildings and libraries that apply biophilic principles. The analysis is descriptive and thematic in order to identify the relationship between biophilic architectural principles, the nature of the science library space, and its impact on users' cognitive, psychological, and social aspects. The research results show that the integration of biophilic elements, both through direct connection with nature, analogies to nature, and spatial experiences, contributes positively to increasing users' concentration, comfort, creativity, and quality of interaction. The biophilic architectural approach has the potential to transform science libraries into sustainable, adaptive, and productive learning environments that are relevant to the social and environmental context of the city of Medan.